Radiological Evaluation of WHO-Defined Pneumonia and Severe Pneumonia - Kader, Md Fazlul; Ahmmad, Be Nazir; Das, Mrinal Kanti; Chowdhury, Mst Ruksana Begum; Sultana, Dilruba; Bari, Md Iqbal; Uddin, Md Belal (TAJ: Journal of Teachers Association, 2023)
In developing countries like Bangladesh, Pneumonia remains a significant cause of morbidity and mortality. In about 50% of cases, no organism can be identified. Therefore, pneumonia diagnosis is usually based on radiographic findings, even in developed countries. World Health Organization (WHO) defines pneumonia based on the clinical Conclusions obtained by chest inspection and respiratory rate of the under-five year children. It was a cross-sectional descriptive type of study conducted in the department of pediatrics in collaboration with the Department of Radiology & Imaging, Rajshahi Medical College, for two years. Chest x-rays with interpretation showed out of 100 patients, 14% were normal, and 31%, 30%, and 25% were suggestive of bacterial Pneumonia, bronchiolitis, and viral Pneumonia, respectively. The chest radiograph is the single most important tool for the diagnosis, exclusion, management, planning of further diagnostic procedures, and follow-up of pneumonia patients. So diagnosis and management of pneumonia are impossible without the use of a chest x-ray evaluation. TAJ 2022; 35: No-2: 111-118